Negotiating Worship Priorities: A Fiqh al-Awlawiyyat Analysis of Al-Azhar Fatwa on Qurban and Aqīqah within Contemporary Economic Contexts - Athambawa, Mahroof; Amin, Abd. Rauf Muhammad (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2026)
Legal tensions between qurban and aqīqah under contemporary socio-economic constraints require a systematic reorientation of worship priorities that balances personal devotional obligations with collective social responsibility. Although classical fiqh literature has discussed the legal status of both rituals, scholarly attention to how authoritative fatwa institutions operationalize methodological tools to reconcile normative texts with modern economic realities remains limited. Therefore, this study aims to examine official fatwa issued by Al-Azhar, a leading reference institution in the Muslim world, focusing on how it formulates priority judgments when Muslims face financial limitations. Using a qualitative design, discursive content analysis was applied to selected Al-Azhar fatwa, which integrate the framework of Fiqh al-Awlawiyyat (jurisprudence of priorities) and the Maqāṣid al-Sharīʿah approach to identify the ratio legis (ʿillat al-ḥukm), supporting Al-Azhar prioritization logic. The results showed that Al-Azhar consistently prioritizes qurban over aqīqah. This is reflected through istislāḥī reasoning that emphasizes qurban as a muwaqqat (time-bound) ritual whose benefits extend beyond the individual to broader communal welfare. The prioritization is further reinforced by the ritual strong association with public distribution, poverty alleviation, and social solidarity, making it more consistent with maṣlaḥah ʿāmmah (public interest) in contexts of economic disparity. The results contribute to contemporary Islamic legal studies by clarifying how Al-Azhar negotiates worship conflicts through priority-based reasoning and proposing a practical normative model for lower-middle-class urban Muslim communities in managing competing devotional practices under financial pressure.